ASSESSMENT OF ELECTRONICS LABORATORY COMPETENCIES USING VIRTUAL OBSERVATION (Proceedings of the International Conference on Education, 2021)
One of the graduate competencies in electronics engineering degree programmes under scrutiny in recent years, and much appreciated by the industry, is the proficient use of electronics laboratory equipment. Some academic institutions conduct their assessment using the observation of student performance while they develop laboratory experiments, whereas other institutions base their assessment on simulators and environments that allow capturing the interaction of students with traditional electronic circuits running on a computer. In contrast, this paper presents a novel approach on assessing electronics laboratory competencies using a remote laboratory, virtual observation and faulty prototyped electronic circuits. The selection of faulty electronic circuits as the instrument for the assessment resulted from coincidences of the graduate competencies declared by the university the authors work for and a survey among company leaders and professionals. Virtual observation consists in gathering information as to how a student uses some software to solve a challenge in order to produce an assessment. Virtual observation has been reported to be successful in substituting physical observation, thus reducing the tedious and error-prone revision of laboratory reports. The use of a remote laboratory allows students to interact with a traditional laboratory at home, while facilitating virtual observation to take place. The paper discusses the competency selected to be assessed and the levels of competency a student can attain based on the performance results. The different candidate faulty circuits as well as the faults to be found by the students are reviewed. Finally, the characteristics, configuration and expected outcomes of the assessment are
Keywords: Higher education; educational innovation; graduate competencies; laboratory; virtual observation